Age and stage of life categorizations used to moralize in online social conflict. (April 2019) - Andersen, Elisabeth Muth; Rathje, Marianne
Highlights: Participants in online fora use age as a resource to negotiate social norms. Participants moralize on conduct in interactions that involve conflict. Age categorization differs in "online" and "offline" settings. Abstract: In much research, age is conceived of as a social fact. Using Membership Categorization Analysis as a methodological framework, this paper investigates how participants in online Facebook groups and discussion fora use age and stage of life categories as a resource to negotiate social norms and moralize on conduct in interactions that involve conflict. We show how age categories are used to link actions and identity categories and how participants use the standardized relational pair 'mother-child' as a justification to moralize. The paper argues that the fact that participants may only have highly limited visual access to co-participants and the fact that participants do not know their co-participants in advance is what makes the use of age and stage of life categorizations to moralize on the conduct of others noteworthy.